Congenital Limb Defects: A Retrospective Cohort Study and Overview of the Literature - Oelmeier, Kathrin; Schmitz, Ralf; Dera, Izabela; Plaßmann, Margit; Braun, Janina; Willy, Daniela; Sourouni, Marina; Köster, Helen Ann; Steinhard, Johannes; Röpke, Albrecht; Klockenbusch, Walter; Möllers, Mareike (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Purpose Congenital limb defects are common malformations that are often associated with other organ defects and genetic disorders. Since prenatal detection is challenging and classification is often complex, the aim of this study was to describe a large cohort of fetuses with congenital limb defects and to identify characteristics that are essential for prenatal evaluation, counselling, and management.Materials and Methods In this retrospective cohort study, all cases of confirmed fetal limb defects from two centers for prenatal ultrasound between 2001 and 2021 were evaluated. Cases with skeletal dysplasia were excluded from this study. Demographic data, association with genetic disorders, and correlation with maternal parameters were analyzed statistically.Results 170 fetuses were included in this study. 60% were diagnosed with a reduction anomaly and 40% with a duplication anomaly. The majority of fetuses were male, and in 73.5% of all cases, additional malformations were present. Among the genetic causes, trisomy 13 and 18 were the most common in this cohort.Conclusion Congenital limb malformations are important markers for complex fetal disorders that warrant referral to specialists in prenatal ultrasound. To improve prenatal detection, care should be taken to visualize all fetal extremities already in early pregnancy.
Keywords: prenatal ultrasound; Congenital limb malformations; genetic counselling